Psicodrama: uma mudança no discurso - Nazare, Maria Helena Pinheiro (1978)
This work connects psychodrama and linguistics. Moreno's opposition, between action and speaking did not seem convincing. Throughout his work, we find references to action that: can be clearly understood under the general title of language. We start with the historic retrospective of psychodrama, its connections with theater, its changing, linking with other theories. Theory of role playing is of great importance. Role is language in action. By reporting a public experience with psychodramatic work, we intend to show the possibility of dealing with several theoretical frames, since they can all be blended by the different functions of language. In the practicing of psychodrama itself what we really deal with is language, and the relation between meaning and its expression.